The universal, collaborative and dynamic model of specialist and advanced nursing and midwifery practice: A way forward?. Issue 5 (1st February 2018) - O'Connor, Laserina; Casey, Mary; Smith, Rita; Fealy, Gerard M; Brien, Denise O'; O'Leary, Denise; Stokes, Diarmuid; McNamara, Martin S; Glasgow, Mary Ellen; Cashin, Andrew
Abstract : Aims and objectives: To inform and guide the development of a future model of specialist and advanced nursing and midwifery practice. Background: There is a sizable body of empirical literature supporting the unique contributions of specialist and advanced practice roles to health care. However, there is very little international evidence to inform the integration of a future model for advanced or specialist practice in the Irish healthcare system. Design: A qualitative study was conducted to initiate this important area of inquiry. Methods: Purposive sampling was used to generate a sample of informants ( n = 15) for the interviews. Nurses and midwives working in specialist and advanced practice and participants from other areas such as legislative, regulatory, policy, medicine and education were included in the sampling frame. Results: Arguments for a new model of specialist and advanced practice were voiced. A number of participants proposed that flexibility within specialist and advanced practitioner career pathways was essential. Otherwise, there existed the possibility of being directed into specialised "silos, " precluding movement to another area of integrated practice. Future specialist and advanced practice education programmes need to include topics such as the development of emotional and political intelligence. Conclusion: The contribution of specialist and advanced practice roles to the health service includes providing rapid access to care, seamless patient flow across services, early discharge and lead coordinator of the patient's care trajectory. There was a recommendation of moving towards a universal model to cultivate specialist and advanced nurse and midwife practitioners. Relevance to clinical practice: The model design has Universal application in a range of contexts "U." It is Collaborative in its inclusivity of all key stakeholders "C." The model is Dynamic pertinent to accommodating movement of nurses and midwives across health continua rather than plateauing in very specialised "silos" "D."